Adequacy of Hemodialysis and Its Associated Factors among Patients Undergoing Chronic Hemodialysis in Dar es Salaam, Tanzania - Somji, Samina S.; Moledina, Sibtain; Ruggajo, Pascal (International journal of nephrology, 2020)
The worldwide prevalence of maintenance hemodialysis continues to rise. An adequate delivery of hemodialysis dose as measured by Kt/V or urea reduction ratio is a crucial determinant of clinical outcome for chronic hemodialysis patients. The aim of this study was to assess the adequacy of hemodialysis and its associated factors among patients undergoing chronic hemodialysis in Dar es Salaam. This was a cross-sectional study done on patients undergoing chronic hemodialysis in four dialysis centers in Dar es Salaam. Sociodemographic information and treatment characteristics were collected. Urea reduction rate and single-pool Kt/V were calculated to determine the adequacy of hemodialysis. The data were analyzed and any associated factors for inadequate hemodialysis were determined using a chi-square test and a logistic regression analysis. A total of 143 patients participated in the study. Males represented 65.7% of the study population. The mean age (±SD) was 51.7 ± 1.2 years. Only 34.3% (based on urea reduction ratio (URR)) and 40.6% (based on Kt/V) of patients received adequate hemodialysis. The univariate analysis showed that males were more likely to have inadequate dialysis (65.6% versus 48.0%, p=0.048 based on Kt/V). Patients using hemodialyzers with dialyzer surface area less than 1.4 m2 received significantly less hemodialysis dose than those with more than 1.4 m2 (69.0% versus 41.2%, p=0.02, by URR) (62.7% versus 35.3%, p=0.03, by Kt/V criteria). Patients who had hemoglobin <10 g/dl received significantly inadequate hemodialysis dose as compared to patients with hemoglobin ≥10 g/dl by Kt/V criteria (69.8% versus 51.3%, p=0.03). None of the factors acquired significance in the multivariate analysis. The proportion of patients receiving an adequate hemodialysis dose is low (34.3% based on URR and 40.6% based on Kt/V). Male gender, dialyzer surface area of <1.4 m2, and hemoglobin level of <10 g/dl were associated with an inadequate delivered dose of hemodialysis in the univariate analysis but not in the multivariate analysis. This study can increase awareness about the importance of measuring hemodialysis adequacy and giving the correct hemodialysis dose to achieve the intended benefit.